Evaluation of the Precision of Emergency Department Diagnoses of Young Children with Fever - Colvin, Joshua M (Clin Pediatr (Phila), 2011)
OBJECTIVE: To characterize causes of fever in otherwise healthy children presenting to a pediatric emergency department (ED). METHODS: One-year retrospective review of ED records. INCLUSION CRITERIA: 2–36 months of age with a documented temperature ≥ 39° C presenting between August 1st,, 2006 and July 31st, 2007. EXCLUSION CRITERIA: elopement, repeat visit in < 1 month or underlying diagnosis with a predisposition to infection. Medical records were reviewed using a predefined, study-specific, data abstraction tool. Based on diagnosis and pathogen detection, visits were assigned to three groups, laboratory confirmed pathogen and focal or non-focal diagnosis without confirmed pathogen. RESULTS: 1091 total visits met inclusion criteria (denominator for all percents). 14% had a pathogen detected: 8% viral and 6% bacterial. 56 % had a focal diagnosis without a confirmed pathogen: 21% otitis media, 13% upper respiratory infection, 7% pneumonia, 16% rarer diagnoses. 30% had a non-focal diagnosis without confirmed pathogen: 15% viral infection not otherwise specified, 8% fever of unknown etiology, 3% febrile seizure, 4% rarer diagnoses. Focal and non-focal diagnoses without detected pathogens had 35% and 61% microbiological tests performed respectively (p<0.001). Admission rates were 49% for patients with confirmed pathogens, 7% with focal diagnoses and 13% with non-focal diagnoses without confirmed pathogen (p<0.001). CONCLUSIONS: In a cohort of febrile children 2–36 months of age evaluated in a pediatric emergency department, only 14% had a confirmed pathogen. New rapid viral diagnostic techniques may provide an opportunity to improve diagnostic certainty in young children presenting with fever.